Impacts of exposure to low concentration of titanium dioxide nanoparticles on cell cycle control and DNA repair in normal, cancer and DNA repair deficient cells. - EL Zahed, Nada (AUC Knowledge Fountain, 2017)
Nowadays, Titanium dioxide nanoparticles, TiO2 NPs, are produced in huge quantities due to their vast range of applications including paints, food coloring, sunscreens and cosmetics. Consequently, humans are exposed to TiO2 NPs on a daily basis. However, the toxicological profile of TiO2 NPs is not fully elucidated. As a result, this study is carried out to evaluate the genotoxic impact of TiO2 NPs on normal, cancer and DNA repair deficient cells. Since most of the studies evaluated the genotoxic impact of the TIO2 NPs have used the acute exposure scenario: High exposure concentrations and short exposure times, in the present study the genotoxic impact of the NPs would be evaluated using the prolonged exposure scenario: low exposure concentration for long exposure time. Cytotoxicity on a cancer cell line was evaluated using the MTT assay, genotoxicity on normal and cancer cell line was evaluated using immunofluorescent staining for anti-Î³-H2AX and anti-total-53BP1, and the impact of the NPs on cell cycle regulation was evaluated using G2/M checkpoint assay on normal and cancer cell lines. In order to study the impact of NPs on DNA repair genotoxicity was evaluated using immunofluorescent staining for anti-Î³-H2AX and anti-total-53BP1 on normal and DNA repair deficient cell lines. Finally, the maintenance of cell cycle G2/M checkpoint in absence of DNA repair genes was evaluated using the G2/M checkpoint assay on DNA repair deficient cell lines. In the present study, we have demonstrated that long exposures to TiO2 NPs does not induces cytotoxicity but it causes significant genotoxicity, particularly DNA double strand breaks. More precisely, we verified that NPs induces DNA DSBs at heterochromatin as well as euchromatin regions of the genome. Furthermore, we demonstrated that DNA DSBs repair, during G1 phase, at heterochromatin region is ATM dependent while DNA DSBs repair at Euchromatin regions is ATM independent, and DNA PKcs and Artemis dependent. On the other hand, it was seen that activation of G2/M cell cycle checkpoint after exposure to the NPs has DNA DSBs dependent-threshold. Also, it was shown that the release of the cell cycle checkpoint has DNA DSBs dependent-threshold. Lastly, we observed cell cycle checkpoint adaptation on prolonged exposure scenario. Taken together, we have demonstrated that prolonged exposure scenario does not affect cell viability but it causes DNA damage and cell cycle checkpoint adaptation leading to genetic instability.